Zakat on business among small and medium entrepreneurs: factors and impact on the business / Jumaelya Jogeran, Shahiszan Ismail and Abd Halim Mohd Noor - Jogeran, Jumaelya; Ismail, Shahiszan; Mohd Noor, Abd Halim (2011)
In Malaysia, the zakat's revenue is one of the factors to equilibrium of economics, especially for zakat on business because it is the most lucrative source of income is earned by businesses. However, the study regarding zakat on business is very small relative to the others zakat. Referring to the Zakat Central Statistics, found there are still many SMEs are not paying zakat. Thus, the research of zakat on business is very crucial to solve the issues related on zakat. This study attempts to identify factors that influence the practice of Zakat among SMEs, and to analyze the impact of the payment of zakat on business and the company. In other words, this research main focus is to identify the cause and factors that result towards poor zakah on business contribution participation among the Muslim Small and Medium Entrepreneurs in Melaka and how does the zakah on business gives impact towards the business. The sample consists of a list of SMEs issued by the relevant zakat center, where the Muslim population is amongst the SMEs in Malacca. Primary data collected from questionnaires and interviews with experts, as well as secondary data collected through zakat institutions, state governments and financial institutions. Data collected will be analyzed using logistic regression which to identify the determinants and to view the possibility weather the SME's entrepreneur comply to zakat practices or not. (Hairunnizam dan Sanep 2005: Mohd Ali 2004: Kamil Md.Idris (2005). This study also uses a logit binomial model to test variable under controlled. The result shows that knowledge is the most significant factor that influence the payment of zakat on business. A few suggestions are also being made to ensure the awareness among the zakat payers increases in the near future.